Editorial: genotype 3 HCV—who still needs ribavirin in a pan‐genotypic era? Authors' reply. Issue 11 (17th May 2018) - von Felden, J.; Vermehren, J.; Schulze zur Wiesch, J.; Sarrazin, C.; Christensen, S.
Abstract : Linked Content This article is linked to von Felden et al and Sadler papers. To view these articles visithttps://doi.org/10.1111/apt.14592 andhttps://doi.org/10.1111/apt.14646 .